Neutrophils in liver diseases: pathogenesis and therapeutic targets - Liu, Kai; Wang, Fu-Sheng; Xu, Ruonan (Cellular & molecular immunology, 2021)
Previously, it was assumed that peripheral neutrophils are a homogeneous population that displays antimicrobial functions. However, recent data have revealed that neutrophils are heterogeneous and are additionally involved in tissue damage and immune regulation. The phenotypic and functional plasticity of neutrophils has been identified in patients with cancer, inflammatory disorders, infections, and other diseases. Currently, neutrophils, with their autocrine, paracrine, and immune modulation functions, have been shown to be involved in liver diseases, including viral hepatitis, nonalcoholic steatohepatitis, alcoholic liver disease, liver fibrosis, cirrhosis, liver failure, and liver cancer. Accordingly, this review summarizes the role of neutrophils in liver diseases.